2021
DOI: 10.3389/fonc.2021.625169
|View full text |Cite
|
Sign up to set email alerts
|

NEDD4 Induces K48-Linked Degradative Ubiquitination of Hepatitis B Virus X Protein and Inhibits HBV-Associated HCC Progression

Abstract: Neural precursor cell expressed developmentally downregulated gene 4 (NEDD4) plays two opposite roles in carcinogenesis. It has been reported that NEDD4 inhibits hepatocellular carcinoma (HCC) progression; however, little is known about its potential function and molecular mechanism in HCC in the context of hepatitis B virus (HBV) infection. In this study, we analyzed NEDD4 expression in 199 HCC specimens with or without HBV infection and observed that NEDD4 expression was unrelated to HBV exposure in HCC tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…For example, NEDD4 can promote the growth and motility of HCC cells by regulating large tumor suppressor gene 1 (LATS1) and phosphate and tension homology deleted on chromosome ten (PTEN)/PI3K/AKT 7 , 28 , 29 ; NEDD4 induces degradative ubiquitination of the hepatitis B virus X protein and inhibits HBV-associated HCC progression. 30 In the present study, we found that NEDD4 and SIAH1 form a complex and that NEDD4 might induce the degradative ubiquitination of SIAH1. We verified that CTSK could also form complexes with NEDD4.…”
Section: Discussionsupporting
confidence: 53%
“…For example, NEDD4 can promote the growth and motility of HCC cells by regulating large tumor suppressor gene 1 (LATS1) and phosphate and tension homology deleted on chromosome ten (PTEN)/PI3K/AKT 7 , 28 , 29 ; NEDD4 induces degradative ubiquitination of the hepatitis B virus X protein and inhibits HBV-associated HCC progression. 30 In the present study, we found that NEDD4 and SIAH1 form a complex and that NEDD4 might induce the degradative ubiquitination of SIAH1. We verified that CTSK could also form complexes with NEDD4.…”
Section: Discussionsupporting
confidence: 53%
“…5C, D). Furthermore, using ubiquitination assays, we noticed that RBCK1-knockdown increased K48-linked ubiquitination of HBx, which has been reported to mediate the proteasomal degradation of HBx [12,23], but decreased the M1-Ubi (Fig. 5E), which may mediate the stability of HBx.…”
Section: Resultsmentioning
confidence: 69%
“…The versatile UPS components, in turn, regulated the stability of HBx via direct or indirect mechanisms [11]. HBx is an unstable protein that is ubiquitinated and rapidly degraded by the proteasome pathway to maintain a very low intracellular level [12,13]. Clinical reports have presented HBx as a possible diagnostic marker by demonstrating its expression in 40% of sera and 85% of liver tissue samples from patients with HCC [14].…”
Section: Introductionmentioning
confidence: 99%
“…4). Posttranslational regulation of hepatitis B virus structural proteins had been an important cellular process during HBV infection, for example, TRIM21 inhibited HBV replication through ubiquitin-mediated proteasomal degradation of HBx 28 , NEDD4 prohibited HBV infection by mediating K48-linked degradation of HBx and inhibits HBV-associated HCC 29 . In addition, deubiquitinating enzyme VCPIP1 binds to HBx protein and promotes stabilization of HBx in a ubiquitin-independent manner by recruiting the PSMC3 in vivo 30 .…”
Section: Discussionmentioning
confidence: 99%